Adoption of Innovative Technology of Tofu Industry and Livestock Waste Products in Rural Area - Tri Anggraeni Kusumastuti; Budi Guntoro (Faculty of Animal Science, Universitas Gadjah Mada, 2006)
File lengkap ada dalam bentuk PDF dibawah ini